Strength training effects on aerobic endurance - Wang, E. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Strength training has the potential to improve work economy, defined as the oxygen uptake (VO2) during a given submaximal exercise. Work economy is one of three factors determining aerobic endurance performance (Pate and Kriska 1984), and if VO2 is seen in relation to the energy cost of the work performed, it is commonly referred to as work efficiency (Barret O'Keefe et al. 2012). When aiming for strength training-induced improvements in work efficiency, intensity appears to be a key component, with high intensity (85-90% of 1RM) being more effective than moderate or low intensity (< 60-70% of 1RM) (Heggelund et al. 2013). As a model of the former, maximal strength training (MST) has been applied in healthy young (Hoff et al. 1999) and old individuals (Wang et al. 2017), and patient populations (Hoff et al. 2007; Husby et al. 2010; Wang et al. 2010). MST is performed at ~90% of one repetition maximum (1RM) with 35 repetitions, 4-5 sets, and maximal intended velocity in the concentric phase of movement. While the majority of the studies that have investigated MST-induced effects on work efficiency have measured pulmonary VO2 during steady-state whole body work, recent studies have provided evidence for the origin or mechanisms of the improvement in work efficiency following MST (Barrett O'Keefe et al. 2012; Wang et al. 2017; Berg et al. 2018). These studies have revealed that 1) the reduction in pulmonary VO2 is caused by a reduction in skeletal muscle VO2, indicating that the mechanisms responsible for the improved work efficiency originate in the trained muscle bed, and are not caused by central adaptations (BarrettO'Keefe, Helgerud et al. 2012); 2) despite metabolic and vascular limb-specific differences, MST-induced improved work efficiency appears to yield similar adaptations in upper and lower extremities, reducing blood flow without changing arteriovenous oxygen difference (Barret O?Keefe et al. 2012; Berg et al. 2018); 3) MST-induced improvements in work efficiency can be achieved despite increases in both percentage and size of Type II muscle fibers and unaltered capillary density (Wang et al. 2017). These findings advocate that MST not only is a great strategy to increase skeletal muscle force-generating capacity, but also to improve aerobic endurance performance, in combination contributing to enhanced health and performance.